Notes on Mr. Elvin's address : inter-departmental correspondence - Elvin, Herbert Henry; Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1938-11-30 1938 1930s 1 page I.C.3. TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From DR. H.B. MORGAN. Department Social Insurance. To MR. J.L. SMYTH. Date 30th November, 1938. SUBJECT. NOTES ON MR ELVIN'S ADDRESS SIC 3 14/12/38. The Address, which starts in a very general way, praises the work of the Voluntary Hospitals and expresses pleasure at the existence of the British Hospitals Contributory Schemes Association "until National Health becomes the affair of a special State Department coordinated with a Ministry of Leisure." The non-representative and non-democratic character of the Hospitals Contributory Schemes is, unfortunately, not stressed sufficiently. It is true that later on a request is made for representation of Trade Unions on Voluntary Hospitals' Committees, but the desirability of a co-ordinated scheme, with National and Central supervision of both types of hospitals, the real democratisation of Voluntary Hospitals, and the adoption of better methods of finance for their support, are not stressed. In this respect a great opportunity is being missed. The reform of the Out-patient Department is urged, and, of course, this is very good; also Post-graduate Courses, called Refresher Courses, for doctors. An interesting point is made for the development of Sub-Clinics, either attached to the Hospitals or the Hospitals themselves, to be linked up with industry; but care is not taken to stress the dangers of what is urged, namely, periodical medical examination from the point of view of the risk of dismissal on alleged medical grounds. The linking too of hospitals with Convalescent Homes and Holiday Centres is stressed. With regard to special diseases, the figures for Cancer are given, but the recent outlined policy of the Government and the establishment of Cancer Clinics is not mentioned. The alleged investigation into Cancer in Sheffield is a purely voluntary act on the part of the Tuberculosis Officer of Sheffield. I think the personal reference to treatment by unorthodox sources and the reference to some unnamed place on the Continent without a reference to what is being done towards bringing the British Spas into line with Continental efforts is a mistake. Many of the British Spas, if the methods could be taken in hand seriously by the Government and by Municipalities, as they are on the Continent, would hold their own with many of the establishments on the Continent. But that stage has not yet been reached. The address is a little bit disjointed and does not reveal a considered, constructive plan as to the proper alignment of Hospitals, Convalescent Homes, Holiday Centres and Spas. International Health. I think Mr. Elvin is handicapped by the fact that he is conscious all the time that he is addressing a particular body making contributions to Hospitals which are unrepresentative and undemocratic. HBM/EKK/132/29.11.38. 292/842/2/221